A practical method of serial bedside measurement of cerebral blood flow and metabolism during neurointensive care. Issue 11 (November 1991) - Sharples, P M; Stuart, A G; Aynsley-Green, A; Heaviside, D; Pay, D A; McGann, A; Crawford, P J; Harpin, R; Eyre, J A
Abstract : Acute encephalopathy is a major cause of death and neurological handicap in children. The principle aims of treatment are to provide adequate cerebral blood flow for the brain's metabolic needs and to prevent intracranial pressure rising above the level at which brain herniation occurs. Rational management requires an understanding of the pathophysiological changes in cerebral blood flow and metabolism which occur. The paucity of data on this subject reflects the perceived difficulty of measuring cerebral blood flow and cerebral metabolism in children. A modification of the Kety Schmidt technique of measuring cerebral blood flow and cerebral metabolism is described. This modification makes it possible to perform serial bedside measurements in children receiving intensive care. This method was used to perform 348 measurements in 58 children. The method was reproducible and no significant complications were encountered. The results indicated that appreciable changes in cerebral blood flow and metabolism could occur in individual patients over time, emphasising the importance of serial measurements. This technique may provide a practical means of monitoring cerebral blood flow and metabolism in very sick children receiving neurointensive care and evaluating the efficacy of treatment.